The Influence of Directors on Financial Performance with Independent Commissioners as a Moderating Variable - Usmany, Paul; Makatita, Josephus Alberth; Bakri, Asri Ady; Usmany, Alfrin E. M.; Cahyono, Ari Nugroho (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Researchers believe that a leader, in this case the Board of Directors, can have a significant influence on the success or failure of a company because it is a leader who plays a big role in the formation of company regulations, the direction of the company, and a leader also oversees these policies so that they can run well and in the desired path including the Financial Performance of a company. Therefore, the research aims to analyze the influence of directors on financial performance. Different from previous research, this research adds the Independent Commissioner variable as a moderating variable which researchers can strengthen the relationship between the Directors variable and Financial Performance. This variable uses 1 Independent variable, namely Directors, one Dependent variable, namely Financial Performance, and 1 moderating variable, namely Independent Commissioner. This research is quantitative with an explanatory approach. The data used in this research is primary data that researchers obtained from distributing online questionnaires to 50 directors, 150 employees and 100 commissioners of private companies spread throughout Indonesia. The results in this article show a positive relationship direction and a significant influence on the Company's Financial Performance because the results are positive and below the significance level of 0.05, namely 0.014..Apart from that, researchers also believe, which is also the second hypothesis in this research, that Independent Commissioners who uphold fundamental principles in the company can moderate the influence of Directors on Financial Performance because the Directors are their subordinates and are under their control. If directors can influence financial performance, then independent commissioners can influence it more significantly because of this structural order. Based on this, the results of the third table of path coefficients show that the Independent Commissioner variable can moderate the influence of the Directors variable on the company's financial performance because it has a positive relationship direction and is below the 0.05 significance level, namely 0.000. More significant than direct testing 0.014. Thus, the first and second hypotheses that the researcher believes can be proven and accepted.